Determining the Factors of Profitability in Islamic and Conventional Banks Of Pakistan: Management Perspective - Mahmood Ali (SEISENSE Journal of Management, 2018)
Banks plays vital role in capitalist economy. During the period of financial turmoil, it has been viewed that banks lost a huge capital due to non-recovery of loans from customers. Since there are two type of banks working in Pakistan therefore this thesis analyse which banks performance was better during the financial crunch between 2008 - 2012. The objective of this thesis is to determine the factor affecting the profitability of Islamic and Conventional banks in Pakistan during the period 2008 – 2012. Data was collected through financial books of seventeen conventional and five Islamic banks. Two dependent variables i.e. Return on Asset and Return on Equity were used to determine the profitability of Islamic and conventional banks in Pakistan. Whereas Liquidity, Credit Risk, Capitalization, Efficiency, Bank Size, Economic Performance, Inflation and a dummy variable were used as Independent variables. Panel Data analysis is used to find out the result of secondary data. Initially the analysis was conducted on whole industry, which then applied on Islamic and Conventional banks separately.